Analisis Dan Perancangan Sistem Inventory Barang Di Kantor Desa Wargasaluyu Berbasis Web - Nur Alamsyah; Budiman .; Hasan Nuraripin (SisInfo, 2020)
The village of Wargasaluyu is structurally under the Ministry of Home Affairs, which has the task of carrying out governance. The village government of Wargasaluyu in carrying out its duties was given the mandate to possess equipment to support its performance. As for the problems that occur in the current system that is for processing data incoming and outgoing goods, data shipping goods, data items are still recorded in the ledger and inventory data inventory is only recorded on a piece of paper and then copied back to the computer by the office , so that sometimes there are difficulties in the calculation of goods and to get information on stock of goods have difficulty sometimes the information provided is not in accordance with the availability of goods. The purpose of this study is to create an Inventory Stock Inventory System, which can manage incoming and outgoing goods, inventory, ordering transactions using the Prototype method and by using a Univied modeling system (UML) for structured modeling. The information system that has been generated in this design can manage data entry and exit goods, inventory data, order transaction data that can be accessed online